2011
DOI: 10.1145/2010325.2010330
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual considerations for motion blur rendering

Abstract: Motion blur is a frequent requirement for the rendering of high-quality animated images. However, the computational resources involved are usually higher than those for images that have not been temporally antialiased. In this article we study the influence of high-level properties such as object material and speed, shutter time, and antialiasing level. Based on scenes containing variations of these parameters, we design different psychophysical experiments to determine how influential they are in the percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…This method has also been successfully applied in a manner similar to ours by Ledda et al [2005], Banterle et al [2009b], Rubinstein et al [2010], and Navarro et al [2011]. Ledda …”
Section: Related Workmentioning
confidence: 74%
See 1 more Smart Citation
“…This method has also been successfully applied in a manner similar to ours by Ledda et al [2005], Banterle et al [2009b], Rubinstein et al [2010], and Navarro et al [2011]. Ledda …”
Section: Related Workmentioning
confidence: 74%
“…Additional statistics that reveal data consistency both within-participant and between-participant are available. Furthermore, the method of paired comparisons has been successfully used in other similar studies [Banterle et al 2009b;Ledda et al 2005;Rubinstein et al 2010;Navarro et al 2011]. For these reasons paired comparisons was chosen as the experimental method.…”
Section: The Experimentsmentioning
confidence: 99%
“…This may be due not only to the lack of flickering artifacts, but also to motion de-blurring mechanisms in our visual system, which make moving images appear sharper than they actually are [42]. This preference seems to be related to the motion blur effect [18]. Future work needs to be conducted to examine the relationship between pre-filtering and motion blur.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Perception The study of visual perception in the context of computer graphics has produced many useful results [14]. Some example applications include selective rendering [15], global illumination [16], [17] and motion blur [18]. Rogowitz and Rushmeier [19] found that simplified geometries were perceived differently for static and animated cases.…”
Section: Previous Workmentioning
confidence: 99%
“…Other properties of the human visual system, such as inattentional blindness and change blindness, have also been utilized for rendering acceleration [29], [30], [31], character animation [32], and tone mapping [33]. Perceptual strategies are also useful in participating media rendering [34], virtual crowd rendering [35], and rendering of motion blur effects [36]. Ramanarayanan et al [37] proposed the visual equivalence predictor for predicting visual differences between images rendered under warped illumination and images rendered under reference illumination.…”
Section: Perceptually Motivated Graphicsmentioning
confidence: 99%